The Analysis of The Role of Traditional Media: A Case Study ofS.Tepsil Shadow Puppets Band, Suratthani Province (The Past Until The 2003 - Present) - เวชวิโรจน์, สุวิมล; หนุมาศ, เหมือนมาด; พรหมทอง, จิรวรรณ; อร่ามศักดิ์, สุธาทิพย์; วุฒิจันทร์, สมปราชญ์ (Journal of Management Sciences Suratthani Rajabhat University, 2018)
a traditional media in Suratthani province. The fiding of the role through the past until the 2003 - present day found that shadow puppets were holding many roles for community and society such as some inherited roles still existing included social images recorded, entertaining, rituals belief,attitude building, and valuable and moral systems and new roles added such as non - formal education assisting in business culture Courses in Educational Institutionsand Cultural participation.